2022
DOI: 10.1021/acs.analchem.2c00411
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dots Tracking Endocytosis and Transport of Proteins Displayed by Mammalian Cells

Abstract: Mammalian cell display technology uses eukaryotic protein expression system to display proteins on cell surfaces and has become an important method in biological research. Although mammalian cell display technology has many advantages and development potential, certain attributes of the displayed protein remain uncharacterized, such as whether the displayed proteins re-enter the cell and how displayed proteins move into the cell. Here, we present the endocytosis mechanism, motility behavior, and transport kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…A protocol was developed to track BODIPY C12-labeled VLDLs’ from a zebrafish embryo yolk sack, and utilizing live fluorescence imaging with the embryos immobilized in agar allowed for the study of the biogenesis, transfer, uptake, and fate of individual endogenous single EVs from the yolk to the other parts of the fish [ 53 ]. Diving deeper into the endocytosis mechanism, by attaching a HaloTag to a platelet-derived growth factor receptor (PDGFR) and expressing the construct in Martin–Darby canine kidney cells, the movement of the growth factor being endocytosed can be accurately tracked [ 54 ]. By associating the HaloTag with a quantum dot, the endocytosis mechanism was visualized through spinning-disk confocal microscopy [ 54 ].…”
Section: Inner and Extracellular Transportmentioning
confidence: 99%
See 3 more Smart Citations
“…A protocol was developed to track BODIPY C12-labeled VLDLs’ from a zebrafish embryo yolk sack, and utilizing live fluorescence imaging with the embryos immobilized in agar allowed for the study of the biogenesis, transfer, uptake, and fate of individual endogenous single EVs from the yolk to the other parts of the fish [ 53 ]. Diving deeper into the endocytosis mechanism, by attaching a HaloTag to a platelet-derived growth factor receptor (PDGFR) and expressing the construct in Martin–Darby canine kidney cells, the movement of the growth factor being endocytosed can be accurately tracked [ 54 ]. By associating the HaloTag with a quantum dot, the endocytosis mechanism was visualized through spinning-disk confocal microscopy [ 54 ].…”
Section: Inner and Extracellular Transportmentioning
confidence: 99%
“…Diving deeper into the endocytosis mechanism, by attaching a HaloTag to a platelet-derived growth factor receptor (PDGFR) and expressing the construct in Martin–Darby canine kidney cells, the movement of the growth factor being endocytosed can be accurately tracked [ 54 ]. By associating the HaloTag with a quantum dot, the endocytosis mechanism was visualized through spinning-disk confocal microscopy [ 54 ]. Live-cell imaging revealed that the HaloTag entered the cells, where the protein moved along microfilaments and microtubules to the lysosomes around the nucleus [ 54 ].…”
Section: Inner and Extracellular Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, HaloTag technology offers a facile and rapid approach to install a bioorthogonal handle on POIs in a highly selective fashion. HaloTag protein is an engineered haloalkane dehalogenase that covalently reacts with synthetic ligands comprising a chloroalkane linker with different functional modalities, such as fluorophores, , drugs, or resins . The covalent conjugation between HaloTag protein and the chloroalkane ligand is highly specific and irreversible in physiological conditions. Therefore, it is desirable to utilize the HaloTag system to develop a protein-immobilized bioprobe for multiple applications.…”
Section: Introductionmentioning
confidence: 99%